Fund Placement and Loan Financing in Sharia Micro-finance: Credit risk analysis (2022-2023) - Rahmat, Rahmat; Abdani, Abdani; Yanuri, Yusuf Rohmat (Indonesian Journal of Islamic Economic Law, 2024)
The purpose of this study is to analyse the credit risk associated with Sharia Microfinance Institutions (MMFIs) in Indonesia. In particular, the study examines the risk associated with fund placement and loan financing over the 2022-2023 period. A qualitative method with statistical analysis is employed to evaluate the relationship between fund placement (the independent variable) and loan financing (the dependent variable). The findings indicate a positive correlation between the two variables, with an increase in fund placement resulting in an increase in loan financing. The analysis also identified downward and upward trends in the Coefficient Adequacy Ratio (CAR) of BPRS, underscoring the significance of risk management with regard to fund placement and microfinance. A decline in the quality of financing could potentially impact liquidity and increase credit risk. This study indicates a negative and symmetrical relationship between NPL BPRS and economic growth in Central Java. However, further investigation is required to ascertain the relationship between NPL BPRS and economic growth in West Java. The findings may assist the OJK and BI in formulating policies to enhance financial stability and safeguard customer funds..